Treating Melanoma Based on the “Cancer Toxin Theory” from the Perspective of the Tumor Microenvironment - Zhou, Xuejie; Wang, Liwen; Tong, Danlei (Journal of Contemporary Medical Practice, 2026)
Melanoma is a malignant skin tumor originating from neural crest-derived melanocytes of the ectoderm. It has an insidious onset and a high mortality rate. The Cancer Toxin Theory is a traditional Chinese medicine (TCM) approach to tumor treatment proposed by Professor Cheng Haibo, based on the academic thought of Master of Chinese Medicine Zhou Zhongying. This theory posits that cancer toxin is the key factor in the occurrence and development of malignant tumors, with the pathogenesis characterized by the accumulation of pathogenic toxins and deficiency of healthy qi. The tumor microenvironment (TME) plays a crucial role in tumorigenesis and progression, and its formation and transformation align with the Cancer Toxin Theory. Guided by this theory, this article elaborates on the characteristics and correlations between the melanoma TME and the pathogenesis of cancer toxin, summarizes the syndrome differentiation-based treatment principles for melanoma under the Cancer Toxin Theory, and provides a reference for TCM treatment of melanoma.